Evaluation and Implementation of IT Governance Using the 2019 COBIT Framework at the Department of Food Security, Agriculture and Fisheries of Balangan Regency - Rini Audia; Bambang Sugiantoro (IJID (International Journal on Informatics for Development), 2022)
The food security, fisheries and agriculture services work with local government to help the community. In carrying out its work, the government applies information technology to achieve the goals. Therefore, it is necessary to have an IT governance design to ensure the alignment of the government’s objectives and the use of IT. Governance is an important asset to measure the effectiveness and efficiency of work process improvement using IT. This research is conducted because there has never been an IT governance design assessment. The analysis and design of IT governance at government agencies are carried out using the COBIT 2019 framework to measure the level of IT capability. The research method used is descriptive qualitative by conducting interviews with influential government parties. This study obtained an IT governance design and detected important processes for the domains used, namely EDM04, APO04, APO07, APO08, APO11, BAI03, BAI08, BAI10.